"A Murmur of Small Voices:" On the Picture Postcard in Academic Research - Ferguson, Sandra (Archivaria, 2006)
This paper attempts to understand why historians and social researchers have traditionally been reluctant to consider the picture postcard as a subject of legitimate research. The few academics who have chosen to study postcards provide clues to the source of this prejudice in their research. The paper outlines the challenges of the postcard within the context of its development in the 19th and 20th centuries. Reviewing academics’ own comments on the use of postcards in their research provides clues as to the postcard’s shifting value as a record. In less than one hundred years, the postcard shifted from a ubiquitous part of daily life to an obscure and occasional academic footnote, and is only now beginning to re-emerge as a valuable documentary form for researchers. Reviewing and analyzing this paradox speaks to the nature of this much neglected but socially important documentary form. RÉSUMÉ L’auteure essaie de comprendre dans cet article pourquoi les historiens et les chercheurs en sciences sociales ont traditionnellement hésité à considérer les cartes postales comme un sujet de recherche légitime. Les quelques chercheurs universitaires ayant choisi d’étudier la carte postale nous donnent des indices sur la source de ce préjugé dans leurs recherches. Cet article donne un aperçu des défis de l’étude de la carte postale dans le contexte de son développement aux 19e et 20e siècles. L’examen des commentaires des chercheurs qui ont étudié les cartes postales donne des indices sur les variations de leur valeur comme document d’archives. En moins de cent ans, la carte postale est passée d’un objet omniprésent de la vie quotidienne à une note de bas de page occasionnelle et obscure dans les travaux universitaires et ce n’est que maintenant qu’elle commence à émerger de nouveau comme forme documentaire valable pour les chercheurs. Analyser et étudier ce paradoxe permet d’appréhender la nature de cette forme documentaire négligée mais importante socialement.